Ligand-based CAR-T cell: Different strategies to drive T cells in future new treatments - Ramírez-Chacón, Alejandro; Betriu-Méndez, Sergi; Bartoló-Ibars, Ariadna; González, Azucena; Martí, Mercè; Juan, Manel (Frontiers in Immunology, 2022)
Chimeric antigen receptor (CAR)-based therapies are presented as cutting-edge treatments for multiple malignancies. Despite their clinical success, there is scientific evidence of the limitations of these therapies mainly due to immunogenicity issues, toxicities associated with the infusion of the product and relapses of the tumour. As a result, new approaches are emerging aiming to solve and/or mitigate the harmful effects of CART therapies. These include strategies based on the use of ligands as binding moiety or ligand-based CAR T cells. Several proposals are currently under development with some undergoing clinical trials to assess their potential benefits. In addition to these, therapies such as CAAR (Chimeric Autoantibody Receptor), BAR (B-cell receptor Antigens for Reverse Targeting), and even CHAR (Chimeric HLA Antibody Receptor) have also emerged, which also aim to benefit from the advantages of ligands as a binding motif. This review aims to focus on the potential role that ligands can play in current and future anti-tumour treatments, but also in other types of diseases, such as autoimmune diseases or rejection problems associated with transplantation.